2014
DOI: 10.1021/nn5031719
|View full text |Cite
|
Sign up to set email alerts
|

Ferroplasmons: Intense Localized Surface Plasmons in Metal-Ferromagnetic Nanoparticles

Abstract: Interaction of photons with matter at length scales far below their wavelengths has given rise to many novel phenomena, including localized surface plasmon resonance (LSPR). However, LSPR with narrow bandwidth (BW) is observed only in a select few noble metals, and ferromagnets are not among them. Here, we report the discovery of LSPR in ferromagnetic Co and CoFe alloy (8% Fe) in contact with Ag in the form of bimetallic nanoparticles prepared by pulsed laser dewetting. These plasmons in metal-ferromagnetic na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 52 publications
5
69
0
Order By: Relevance
“…Since the contrast in HAADF image comes from its atomic number (Z) dependence, the bright region in the NSs corresponded to Ag while the darker regions corresponded to Co. The elemental identification was also verified using EELS, as described by us previously for such bimetal systems . In those works performed on glass substrates, we showed that a clear phase segregation of Ag and Co was present in ns‐PLDew NSs, very similar to our observations here for the C substrate.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Since the contrast in HAADF image comes from its atomic number (Z) dependence, the bright region in the NSs corresponded to Ag while the darker regions corresponded to Co. The elemental identification was also verified using EELS, as described by us previously for such bimetal systems . In those works performed on glass substrates, we showed that a clear phase segregation of Ag and Co was present in ns‐PLDew NSs, very similar to our observations here for the C substrate.…”
Section: Resultssupporting
confidence: 89%
“…The elemental identifi cation was also verifi ed using EELS, as described by us previously for such bimetal systems. [ 26,27 ] In those works performed on glass substrates, we showed that a clear phase segregation of Ag and Co was present in ns-PLDew NSs, very similar to our observations here for the C substrate. In Figure 4 b, a plan-view HAADF image of bimetallic Au-Co NSs on C is shown.…”
Section: Large-area Coverage Of Nsssupporting
confidence: 89%
See 2 more Smart Citations
“…Bimetallic materials are a promising new way to realize new and/or better plasmonic behaviors [3,4]. In this paper we first use high-resolution transmission electron microscopy to present evidence for ferroplasmons, strong surface plasmons that appear in ferromagnetic metals when in the proximity of noble metal nanostructures.…”
mentioning
confidence: 99%